Demographic and clinical characteristics of hospitalised unintentional poisoning in Aboriginal and non-Aboriginal preschool children in New South Wales, Australia: a population data linkage study. Issue 1 (30th January 2019) - Lee, Caroline; Hanly, Mark; Larter, Natasha; Zwi, Karen; Woolfenden, Susan; Jorm, Louisa
Abstract : Objectives: To investigate differences in demographic and clinical characteristics of Aboriginal and non-Aboriginal children aged 0–4 years hospitalised for unintentional poisoning in New South Wales (NSW), Australia. Design and setting: Retrospective whole-of-population cohort analysis of linked hospital and mortality data for 2000–2014. Participants: All children (Aboriginal and non-Aboriginal) under the age of 5 years who were born in a hospital in NSW from 2000 to 2009. Outcomes: The primary outcome was hospitalisation for unintentional poisoning. Logistic regression was used to estimate odds of poisoning hospitalisation for Aboriginal and non-Aboriginal children. Poisoning agents and clinical outcomes were compared by Aboriginality. Results: The cohort included 767 119 children, including 28 528 (3.7%) Aboriginal children. Aboriginal children had approximately three times higher rates of hospitalised poisoning (1.34%) compared with non-Aboriginal children (0.41%). Poisoning incidence peaked at 2–3 years of age. Male sex, socioeconomic disadvantage and geographical remoteness were associated with higher odds of poisoning hospitalisation for Aboriginal and non-Aboriginal children, but associations with disadvantage and remoteness were statistically significant only for non-Aboriginal children. Most (83%) poisonings were caused by pharmaceutical agents. Few Aboriginal and non-Aboriginal children had repeat admissions for poisoning; most had a length of stay of 1 day or less. Only 8% of poisoning admissions involved contact with a social worker. Conclusion: Commonly used medications in the general population contribute to poisonings among both Aboriginal and non-Aboriginal preschool-aged children. This study highlights a need to develop culturally safe poisoning prevention strategies and policies.